(untitled) (Swiss Medical Weekly, 2024)
AIMS OF THE STUDY: Unlicensed drugs are frequently used in paediatric care. To what extent they are prescribed in hospital care in Switzerland is unclear. Because prescribing errors seem to occur more frequently with unlicensed drugs, we aimed to assess the prevalence of unlicensed drug prescriptions in two study periods (2018 and 2019) at the University Children’s Hospital Zurich, compare these periods and investigate whether unlicensed drugs were more prone to prescribing errors than licensed drugs. METHODS: We conducted a sub-analysis of a retrospective single-centre observational study and analysed 5,022 prescriptions for a total of 1,000 patients from 2018 and 2019 in paediatric general wards. The rate of unlicensed drugs, consisting of imported or formula drugs, was investigated. The prescriptions from 2019 were further analysed on prescribing errors to see whether errors occurred more often in unlicensed or licensed drug use. RESULTS: Of all prescriptions, 10.8% were unlicensed drugs, with around half each being imported and formula drugs. Among all patients, 34% were prescribed at least one unlicensed drug. Younger paediatric patients were prescribed more unlicensed drugs than older paediatric patients (newborns: 15.8% of prescriptions, infants: 13.4%, children: 10.6%, adolescents: 7.1%). Ibuprofen suppositories, midazolam oral solution and gentamicin i.v. solution were the most frequently prescribed imported drugs. Macrogol powder, lisinopril oral suspension and potassium chloride i.v. solution were the most frequently prescribed formula drugs. The most common drug forms in unlicensed use were oral liquid forms and i.v. solutions. Unlicensed drugs had a significantly higher rate of prescribing errors than licensed drugs (31.6 errors per 100 prescriptions [95% CI: 26.1–37.0] versus 24.3 errors per 100 prescriptions [95% CI: 22.3–26.2], p = 0.024). In particular, formula drugs carried a higher risk (36.4 errors per 100 prescriptions, p = 0.012). CONCLUSIONS: Unlicensed drugs are frequently prescribed in this paediatric hospital setting in Switzerland. Around every tenth prescription is an unlicensed drug. Because unlicensed drugs showed a significantly higher rate of prescribing errors, licensed drugs are favourable in terms of medication safety and should be prescribed whenever possible. If no licensed drug is available, imported drugs should be favoured over formula drugs due to lower prescribing error rates. To increase medication safety in paediatrics in Switzerland, efforts are necessary to increase the number of suitable licensed drug formulations for paediatric patients, including developing new innovative drug formulations for children.